The Effectiveness of Scrapbook Media on Improving Students' Reading Comprehension Skills - Nayla Rosyidah Zahroh; Sumarniningsih Sumarniningsih (Universitas Galuh, 2026)
Reading comprehension is an important competency in EFL learning, but the ability of most students in a private junior high school in Surabaya still has difficulty with reading comprehension activities in descriptive texts. This condition has prompted the need for innovative learning media, such as scrapbook media, a visual medium combining pictures, short texts, and interactive elements. This study examined the significant difference in reading comprehension improvement between students taught with and without scrapbook media and measured the magnitude of its effect. A two-group pretest-posttest quasi-experimental design was employed with 60 seventh-grade students (experimental and control group) and using a 20-item multiple-choice test as the instrument. Both groups started with an identical pretest mean of 54.50, confirming comparable initial abilities. After treatment, the experimental group outperformed the control group, with a higher posttest mean (80.17 vs. 68.33). Then, since the data were not normally distributed, the Mann-Whitney U test was selected as a non-parametric alternative, yielding P = 0.000 < 0.05 and confirming a statistically significant difference. The effect size (r = 0.55) indicated a large practical impact, meaning the improvement was educationally meaningful. N-Gain scores of 0.56 and 0.32 both indicate medium improvement, yet the experimental group improved almost twice as much. Thus, scrapbook media is both statistically and practically effective in improving reading comprehension of descriptive texts and is recommended as an alternative learning medium for the English language.